2011
DOI: 10.1016/j.jpurol.2011.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Miniature pyeloplasty as a minimally invasive surgery with less than 1 day admission in infants

Abstract: Miniature pyeloplasty is a safe and successful technique for ureteropelvic junction obstruction that avoids long operative time with negligible postoperative pain compared to the classic open pyeloplasty in infants. The exact incision site must be reconfirmed intraoperatively by physical examination or renal ultrasonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Wu Y et al in a recent meta-analysis, showed that there are no differences between the laparoscopic and retroperitoneoscopic technique in terms of success and complication rate, although the transperitoneal approach provides a shorter operative time and lower conversion rate [10]. It is also starting to show up the use of robotic-assisted procedures [11]- [13] which at the moment is burdened by very high costs, long learning curve and longer time of execution.…”
Section: Discussionmentioning
confidence: 99%
“…Wu Y et al in a recent meta-analysis, showed that there are no differences between the laparoscopic and retroperitoneoscopic technique in terms of success and complication rate, although the transperitoneal approach provides a shorter operative time and lower conversion rate [10]. It is also starting to show up the use of robotic-assisted procedures [11]- [13] which at the moment is burdened by very high costs, long learning curve and longer time of execution.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is relevant that the procedure can be performed via such a small approach in infants to be called "minimally invasive open pyeloplasty" (40)(41)(42). Chako et al reported that in patients <5 years, the procedure can be performed via an incision <3 cm in about 100 min on average combining a quick procedure with good cosmetic outcome (42) (Figure 3).…”
Section: Pyeloplasty In Infantsmentioning
confidence: 99%
“…A small incision limits exposure of the anatomical structures, which can be an issue in case of unexpected anatomical variants. For this reason, advocates of this approach have underscored the importance of determining the exact incision site by intraoperative renal ultrasonography (40), and/or performing a retrograde pyelogram at the beginning of the surgery to define exactly the PUJ anatomy (41). Otherwise, a minimally invasive approach might prove somewhat more flexible while dealing with unexpected variants.…”
Section: Pyeloplasty In Infantsmentioning
confidence: 99%
“…Therefore, we consider that open dismembered pyeloplasty using a retroperitoneal approach is the most effective and safest surgical procedure. In open surgery, the ureteropelvic neoanastomosis is possible through a small wound in infants and young children with smaller body sizes because the distance between the body surface and the UPJO is short 7,8 . However, in older children with larger body sizes it is difficult to perform the procedure through a small wound because the distance between the body surface and the UPJO is long.…”
Section: Introductionmentioning
confidence: 99%